STUDY OF CRACKERS INDUSTRY IN KENAGARIAN TARUNG-TARUNG KECAMATAN RAO KABUPATEN PASAMAN - Mustika, Mega; Erita, Yeni; Farida, Farida (Pendidikan Geografi, 2014)
Abstracts                                                                                                                                                   The aims of ithis study to look at the cracker business in the Kenagarian Tarung - Tarung Pasaman Rao . The problem that often ariset are a lack of capital , production processes and products . The low production of crackers can be seen from the lack of quality of produced goods and raw materials that are difficult to get . This research is a descriptive study used, a method of research / troubleshooting procedure melakskan investigated by describing the state of the business and industry based on the facts that appear or as they are. The sample used a total of 20 sampling cracker industry entrepreneurs . Data were collected through observation and questionnaires were used to look at the existing industrial business crackers in Kenagarian Tarung-Tarung. Availability of capital cracker industry in Kenagarian Tarung - Tarung craftsmen with a percentage of 40% . Industrial processes crackers bambang seen from the production process is one week , the manufacturing process using the mold as much as 65 % of the respondents . And industrial results Bambang crackers can be seen from the amount of production in the production of as much as 100-200 times 1 pack per day , with a 75 % sales gain from the sale of crackers .